Equity and Government Bond Relationship in Indonesia During Covid Pandemic - Gracia Shinta S. Ugut; Liza Handoko; Kristina Vaher (APTISI Transactions on Management (ATM), 2026)
This study extends prior Covid-19 finance literature by examining the dynamic relationship between Indonesian equity returns and sovereign benchmark bond returns using daily data across two pandemic waves. Unlike previous studies focusing primarily on developed markets or conventional flight-to-safety behavior, this study provides evidence that government bonds in emerging markets may temporarily exhibit equity-like risk characteristics during pandemic-induced fiscal stress. Specifically, the findings show that equity market performance is positively correlated with government bond returns in Indonesia during the two waves of the Covid 19, as opposed to the findings from previous studies when there were financial crises, and also the results show negative correlation between the government bond return and the spread of the Credit Default Swap. Furthermore, this study examines the impact of the Covid pandemic to the local Indonesian long-term and medium-term benchmark bonds after applying the international risk factor variable to the model. The results show shifting investors’ attention from the international risk factors to the local risk factors in both medium and long tenor of the bonds during the pandemic period. Overall, this study highlights how pandemic-induced fiscal uncertainty alters stockbond dynamics in emerging markets and challenges conventional safe-haven assumptions regarding sovereign bonds.